2009
DOI: 10.1007/s10529-009-0143-x
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of α-amyrin into centellosides by plant cell cultures of Centella asiatica

Abstract: Plant cell cultures of Centella asiatica produce small quantities of centellosides: madecassosid > asiaticosid > madecassic acid > asiatic acid. To obtain a more efficient production system of these bioactive triterpenoid compounds, we developed a process where the substrate, alpha-amyrin, was converted into centellosides by cell suspensions of C. asiatica. When alpha-amyrin in acetone was added at 0.01 mg/ml(-1) to the culture medium, together with the permeabilizing agent DMSO, after 7 days nearly 50% had pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…The DW of control cells increased three-fold on day 10, remaining largely unchanged until day 25, when it began to decrease, probably due to the depletion of nutrients in the culture medium. Similar growth courses have been previously described for C. asiatica cell cultures (Nath and Buragohain 2005;James et al 2008;Hernández-Vázquez et al 2010). The elicited cells (100 and 200 lM MeJA) showed a similar growth pattern to the control but with lower values and a decrease from day 15.…”
Section: Resultsmentioning
confidence: 63%
See 1 more Smart Citation
“…The DW of control cells increased three-fold on day 10, remaining largely unchanged until day 25, when it began to decrease, probably due to the depletion of nutrients in the culture medium. Similar growth courses have been previously described for C. asiatica cell cultures (Nath and Buragohain 2005;James et al 2008;Hernández-Vázquez et al 2010). The elicited cells (100 and 200 lM MeJA) showed a similar growth pattern to the control but with lower values and a decrease from day 15.…”
Section: Resultsmentioning
confidence: 63%
“…4), which shows a delay between the activation of this gene and centelloside production, suggesting that, although CabAS is a key enzyme, it does not represent a limiting step in the centelloside biosynthetic pathway. It is also noteworthy that the carbon skeleton of centellosides like asiaticoside and madecassoside is more related with the a-amyrin skeleton than the b-amyrin skeleton (Hernández-Vázquez et al 2010;Kim et al 2010). Therefore, the up-regulation of CabAS gene expression after MeJA treatment could play a major role in the biosynthesis of other centellosides, such as centellasaponin A, asiaticoside B etc.…”
Section: Free Sterol Production In Control and Elicited Cellsmentioning
confidence: 99%
“…CaSQS, CabAS, and CaCYS genes play important roles in the biosynthesis of phytosterols and triterpenoid in centella. CabAS is a key gene for triterpenoid regulation, whereas CaCYS gene responds for phytosterols synthesis (Hernandez-Vazquez et al 2010 ). In previous report, we showed that salicylic acid elicitation enhanced asiaticoside accumulation, a type of triterpenoid, especially at concentration of 100 µM (Loc and Giang 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Cell cultures at the mid to late log phase of growth were treated with dimethyl sulfoxide (DMSO) or DMSO plus a-amyrin dissolved in acetone [58]. DMSO alone was capable of effectively permeabilizing cells, increasing eight-fold the total centelloside content in medium.…”
Section: Environmental Control Of Triterpenoid Saponin Productionmentioning
confidence: 99%
“…The same treatment also had a positive effect on centelloside production, increasing it by 213% relative to control concentrations. The combined application of DMSO and a-amyrin (1% v/v and 0.01% mg/ml) improved the total centelloside content by approximately four-fold, presumably due to improved uptake of a-amyrin [58]. Besides showing that a-amyrin is an adequate substrate for conversion into centellosides, these experiments suggested that enzymes involved in later steps of centelloside biosynthesis are not the bottleneck for low product formation in control cell cultures in presence of adequate substrate amounts.…”
Section: Environmental Control Of Triterpenoid Saponin Productionmentioning
confidence: 99%